TRANSLATION PROBLEMS OF FICTION - Haydarova Ro`zixol (Zeta Repository, 2023)
There is an increasing demand for translation of children’s literature nowadays and this demand is accompanied by an increased need for the researchers to study the nature and feature of such a discipline. It is worth mentioning that the word “children’s literature” in English-speaking countries is a broader term covering children, adolescents and sometimes young adults. The present paper aims to highlight some comprehensive theoretical aspects concerning children’s literature translation. Special attention is paid to the issues which have generated lots of intense and ongoing debates among theoreticians as to which translation strategies and procedures would be more beneficial to the target language child reader. Before elaborating on such issues, this paper casts some light on the various definitions of children’s literature and its characteristics, its status and the role it exerts on the potential readership. Ambivalence of children’s literature – the texts being addressed to both children and adults – constitutes one of the biggest challenges for the author and the translator of children’s literature alike. Such a phenomenon is investigated in this paper illustrated with some book titles. Another feature which is tackled in this paper is that of asymmetry, which refers to the unequal communication levels between adults and children. Finally, conclusions will be drawn regarding to most popular theoretical trends of children’s literature and children’s literature translation.